Determining and reporting minimal important change for patient-reported outcome instruments in pulmonary medicine. Issue 4 (20th October 2022) - Swigris, Jeff; Foster, Brandon; Johnson, Nathan
Utilising consistent terminology and a rigorous approach to determining and reporting minimal important change to the patient (MICP) would elevate quality of measurement science in our field and bolster confidence in using PROs as first-tier endpoints https://bit.ly/3OOGNhc